Influence of ion structure and solvent electric dipole on ultrananoporous supercapacitor: a lattice model study. (1st August 2022) - Zhou, S; Zhou, R
Abstract: A five-state modified BEG model is proposed for describing electrolyte in polar solvent in cylindrical electrode pore in which only one row of particles can be stationed. Two properties the closest to the actual situation of the aqueous electrolyte are integrated into the model: cation is dimer comprised of two tangentially tethered hard spheres of different diameters: one is charged, while the other is neutral, and polar solvent is modeled as neutral hard sphere with an electric dipole. The system partition function is obtained by numerically solving maximum real root of characteristic equation of 25 × 25 Kramers-Wannier transfer matrix. The model is used to investigate effects of ion structure and electric valence, solvent electric dipole, and cylindrical pore radius on specific differential capacitance C d and specific energy storage E of the resulting supercapacitor. Main findings are briefly described below. (i) The dimer counter-ion electric valence does not exert obvious influence on the saturation value E s a t of the E, but reduces the threshold electrode potential strength U s a t, beyond which the E s a t value is just reached. (ii) Whether the dimer counter-ion is monovalent or bivalent, the C d peak height and the E s a t value tend to rise with the dimer neutral site size d + 0 decreasing, but influence of the d + 0 value on the U s a t value is very small. Only when the d + 0 value is small enough, the U s a t value rises a little with decrease of the d + 0 value. (iii) Increase of solvent electric dipole moment (whether by increasing the dipole charge or dipole length) always raises the E s a t value, and enlarges width of the pure solvent domain or zero C d and zero E domain around the zero electrode potential, but does not change the U s a t value obviously. (iv) With the pore size increasing, the E s a t value reduces and the U s a t value increases. So, using small size pore is favorable to improve the supercapacitor performance from the perspective of energy storage and electrode potential applied. (v) The three parameters: d + 0, dipole charge, and dipole length, are cooperative in influencing the E s a t value.